Prevalence of atherosclerotic lesions of the brachiocephalicarteries and their association with cardiovascular risk factors: a cross-sectional study in uzbekistan (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. To assess the prevalence of atherosclerotic lesions of the brachiocephalic arteries (BCA), their association with cardiovascular risk factors, and cardiovascular risk according to the SCORE scale in the population of Uzbekistan. Materials and methods. A cross-sectional study (conducted in 2025 using 2022 data) included 6,425 patients (47.6% men, 52.4% women; mean age 54.0 ± 23.1 years) at the Republican Specialized Scientific and Practical Medical Center of Cardiology, Uzbekistan. Carotid and brachiocephalic ultrasound was performed using a short protocol assessing stenosis in four segments [1]. The following parameters were analyzed: age, total cholesterol (TC), arterial hypertension (AH), smoking, systolic and diastolic blood pressure (SBP, DBP). Cardiovascular risk was determined using the SCORE system [2]. Statistical analysis was performed using SPSS 26. Results. BCA lesions were detected in 54.8% of patients. Age correlated with the presence of lesions (Spearman’s ρ = 0.219, p < 0.01), while TC did not (ρ = 0.032, p = 0.207). Men over 50 years had more extensive lesions (7.9% with four affected segments) compared to women (2.6%). According to the SCORE scale, men and patients over 50 years had a moderate to high cardiovascular risk (4–8%). Conclusion. Age is the key risk factor for atherosclerosis of the brachiocephalic arteries. The high prevalence of arterial hypertension emphasizes the need for preventive measures in Uzbekistan.